PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN NILAI-NILAI KARAKTER SISWA KELAS X MIA SMA NEGERI 12 PEKANBARU TAHUN PELAJARAN 2014/2015 - Zul Arifin; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the effect of group counseling services to increase the values of character class X MIA SMA 12 Pekanbaru school year 2014/2015. This research was conducted in SMA 12 months Pekanbaru from March 2015 to May 2015. The method used was experimental method to pattern one-group pretest-posttest. That is the subject in the study were a number of students of class X SMA Negeri 12 Pekanbaru MIA totaling 30, the subject of research in select purposively in accordance with the characteristics of the subjects to be researched is the practice that has the character values are lowest. Instrument in this study was a questionnaire about the practice of the values of the characters. This questionnaire consists of 40 items on the practice of the values of character with alternative